Lighter weight and energy efficient eco-siC composite for motorbike brake disc application - Maleque, Md. Abdul; A.R., Nur Farina; Paijan, Lailatul Harina; Abdullah, M. Azwan (2018)
The novelty of this invention is to use eco-SiC as reinforcement for composite motorbike disc application with the aim to reduce weight, enhance energy efficiency and save fuel consumption of motorbike and utilize waste rice husk for the source of eco-SiC. Simple and cost effective green production technique which reduces hazardous CO2 gas compared to ferrous cast iron production.